Diabetic nephropathy and its related factors in FELDA Chini, Pahang - Amran, Nur Azyyati Amani; Hanapi, Khalijah; Abdul Aziz, Nuramira; Kamaruzaman, Nor Azam; Pasi, Hafizah (2017)
Introduction: Diabetic nephropathy is currently becoming a concern. Multiple studies show that there is rising in its complications especially in patients requiring dialysis due to diabetic nephropathy. In Felda Chini limited studies done on diabetic nephropathy among diabetes patient in Felda Chini and the factors related to it. Objectives: To describe prevalence of diabetic nephropathy patient in Chini and to describe sociodemographic of patient with diabetic nephropathy thus identify its related risk factors and the association between them. Methodology: This is a comparative cross-sectional study done on 202 diabetic patients Felda Chini done in Outpatient Department, KK Chini from April to July where data is recorded from Diabetic Record Book. Data collected then analysed using SPSS Version 22.0. The relationship between variables was tested using chi-square test. Results and Discussions: In this study, total of 202 respondents were involved. Most of our respondents were from middle age population, 53.5% are from 41-60 years old group and female gender which is 59.4% consistent with NHMS 2015.In this population, most respondents are in Pre-Obese category which is 37.1% and reflected the general population. Meanwhile the other two variables that we measure is control in hypertension and diabetic control. Both types of control HbA1c and BP control has poor control with HbA1c has 82.7% has poor control and 53.5% of respondents has poor BP control. The study shows that most of the respondents have normoalbuminuria (44.1%) consistent with a cohort study in 2006 by NCT Kong et al. However, compared to the study where only 15.7% has overt proteinuria instead in this study 35.1% of our respondents have overt proteinuria. Most of our respondents has CKD stage I-II(72.8%) while 27.2% of the respondents has CKD stage III-IV comparatively similar to a study done by Ferguson TS et al where 22% of the respondents have GFR <60 which is at least stage III CKD. We found out that male gender has significantly related to development of proteinuria(χ²=14.24,df(2) p=0.001). and GFR (χ²=11.80,df(1) p=0.001). This is consistent with a study of Risk Factors for Renal Dysfunction in Type 2 Diabetes mellitus by Ravi R et al. showing that male gender has higher risk of developing microalbuminuria and in a study on influence of sex on renal function decline in people with Type 2 Diabetes by Hautecloque et al shows that male gender plays important role as an associated factor to develop end stage renal disease. Old age was also found out to be related to reduced creatinine clearance in this study (χ²=5.13,df(1) p=0.024) consistent with most of the studies on diabetic nephropathy where age affected creatinine clearance. BMI, HbA1c , BP control however did not affected much the population in this study. No significant association noted between these risk factors with neither proteinuria nor creatinine clearance. Conclusion: The risk factors associated with development of diabetic nephropathy in this population is mainly the non-modifiable risk factors which are older age and male gender and no significant association between modifiable risk factors such as HbA1c control BP control BMI with development of nephropathy. This is might be due to limitation in population sample which only involves one clinic. Further study can be done with larger scope which can involve multiple clinic with similar setting.